Basketball and ankle injuries - Falcone, G.; Scurati, R.; D'Elia, F.; D'Isanto, T. (Journal of Human Sport & Exercise, 2019)
The aim is to demonstrate how an ankle injury appears to be a serious problem and that, as such, it must be adequately addressed to prevent it from recurring in the future because, as evidenced by recent studies, the risk of a relapse it is greater if there are precedents not completely rehabilitated. This study also wants: 1) to list all the factors that predispose the onset of an ankle injury; 2) describe the different types of ankle injuries; 3) set out guidelines on prevention and post-injury recovery. Finally, we will see how accidents in basketball are almost identical for both professional athletes and occasional practitioners of this discipline. Injuries cannot be completely prevented because given the variability of factors it's really great and it`s almost impossible to make an accurate prediction on a specific joint. Performing specific exercises, however, is a great way to minimize the chance of an injury and consequently increase the physical and mental health of the athlete.